2019
DOI: 10.1155/2019/9594369
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Uptake Efficiency and Total Soil Nitrogen Accumulation in Long-Term Beef Manure and Inorganic Fertilizer Application

Abstract: Livestock manure is a common soil amendment for crop-livestock production systems. However, the efficiency of crop nitrogen (N) uptake from the manure-amended soil may not equate with that from inorganic N sources. The objective of this paper was to determine the efficiency of N uptake, grain yield, and total soil nitrogen (TSN) accumulation in beef manure-amended soil compared to the inorganic N fertilizer-amended soil. Data (1990–2015) from a long-term continuous winter wheat (Triticum aestivum L.) fertility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 32 publications
2
5
0
2
Order By: Relevance
“…However, it is known that the excessive application of mineral and synthetic fertilizers in intensive farming systems has led to nutrient accumulation in soils and groundwater, which is responsible for a decrease of soil organic matter (OM) (SVANBÄCK et al, 2019;OMARA et al, 2019). Nardi et al (2004) verified that only farmyard manure fertilization maintained total organic carbon level of 40 t C ha -1 , measured in topsoil layers at the start of a 40-year experiment, while the average total organic C depletion was 43% with mineral fertilizers.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is known that the excessive application of mineral and synthetic fertilizers in intensive farming systems has led to nutrient accumulation in soils and groundwater, which is responsible for a decrease of soil organic matter (OM) (SVANBÄCK et al, 2019;OMARA et al, 2019). Nardi et al (2004) verified that only farmyard manure fertilization maintained total organic carbon level of 40 t C ha -1 , measured in topsoil layers at the start of a 40-year experiment, while the average total organic C depletion was 43% with mineral fertilizers.…”
Section: Introductionmentioning
confidence: 99%
“…Soil organic carbon and TSN are indicators of soil quality and provide structural stability to the soil matrix. However, there is a significant reduction in the rate of buildup and possible depletion under the CT system [8,9]. Halvorson et al [10] reported a decreasing pattern in SOC as NT < MT < CT where the most SOC is retained under NT.…”
Section: Introductionmentioning
confidence: 99%
“…El N es nutriente muy dinámico que se pierde con gran facilidad, es el más def iciente en los sistemas agrícolas (Omara et al, 2019), lo cual puede constatarse en el Cuadro 4 con niveles bajos en la mayor parte de los sitios. A diferencia del P, el N no tiene la misma capacidad de acumularse en el suelo.…”
Section: Resultados Y Discusiónunclassified